Volatile Photovoltaics: Green Industrialization, Sacrifice Zones, and the Political Ecology of Solar Energy in Germany. Issue 6 (19th September 2021) - Brock, Andrea; Sovacool, Benjamin K.; Hook, Andrew
Abstract : The development of solar energy has been depicted as a paradigmatic break in unsustainable global growth, largely because it is framed as an innovation with minimal carbon emissions. On the contrary, drawing on literatures from spatial justice and political ecology, including on authoritarian populism, this article analyzes the rise and fall of the solar industry and the associated failures of "green industrialization" in Bitterfeld, East Germany—an area that is characterized by political, economic, and social peripheralization, marginalization, and the rise of the far right. The development of solar energy, we argue, is merely the latest iteration of an industrial growth model that is rooted in a similar modernist mode of development. Based on original mixed methods field research in eastern Germany, it argues that many of the same inequalities that characterize fossil fuels and "gray" (de)industrialization—undemocratic and unsustainable industrial processes, the concentration of corporate power and profits, and externalized waste and pollution—are replicated by solar energy. What is distinct is the fact that such contemporary "green" manufacturing processes appear to negatively affect a wider and more dispersed range of spatial locations, also denying these locales the benefits of accumulation, production, and consumption. This unevenness reflects the reconfiguration of global supply chains over the past thirty years and the nature of green production processes that depend on a wider range of inputs that invariably produce localized sacrifice zones. We offer a spatial justice framework for solar energy, zooming in at the manufacturing stage, to explore the multiple sacrifice zones at the different stages of solar energy. Finally, we highlight the politics of resignation that is the product and foundation of capitalist realism that serves to dispossess communities around solar energy manufacturing sites in eastern Germany and might feed into the rise of the populist far right. The article contributes to the emerging critical literature that analyzes the dark side of renewable energy and, in doing so, reveals the social and ecological costs of energy transitions that continue to be underresearched yet deserve heightened attention.